2019
DOI: 10.1002/med.21563
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary approaches for targeting the secretase protein family as a therapeutic route for Alzheimer's disease

Abstract: The continual increase of the aging population worldwide renders Alzheimer's disease (AD) a global prime concern. Several attempts have been focused on understanding the intricate complexity of the disease's development along with the on‐ andgoing search for novel therapeutic strategies. Incapability of existing AD drugs to effectively modulate the pathogenesis or to delay the progression of the disease leads to a shift in the paradigm of AD drug discovery. Efforts aimed at identifying AD drugs have mostly foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 290 publications
0
11
0
Order By: Relevance
“…This necessitates the need for the design of diverse molecular libraries with high 3D‐content to crosstalk specifically with the high 3D‐content complementary in BACE1. This conclusion is supported by several examples of successful drug discoveries, which indicated that increasing the SP 3 ‐contents of a ligand to better suit the complementary binding regions of an active site correlates favorably with selectivity and the success rate in clinical trials . Moreover, recent reports illustrated that BACE1 inhibitors caused structural and functional synaptic impairment that accounts for safety concerns .…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…This necessitates the need for the design of diverse molecular libraries with high 3D‐content to crosstalk specifically with the high 3D‐content complementary in BACE1. This conclusion is supported by several examples of successful drug discoveries, which indicated that increasing the SP 3 ‐contents of a ligand to better suit the complementary binding regions of an active site correlates favorably with selectivity and the success rate in clinical trials . Moreover, recent reports illustrated that BACE1 inhibitors caused structural and functional synaptic impairment that accounts for safety concerns .…”
Section: Discussionmentioning
confidence: 80%
“…This conclusion is supported by several examples of successful drug discoveries, which indicated that increasing the SP 3 -contents of a ligand to better suit the complementary binding regions of an active site correlates favorably with selectivity and the success rate in clinical trials. [195][196][197] Moreover, recent reports illustrated that BACE1 inhibitors caused structural and functional synaptic impairment that accounts for safety concerns. 106 Additionally, emerging evidence is exposing gender as a factor to be considered when designing therapeutic option for AD, 198 which requires further investigations to determine how this element can better shape AD therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Alzheimer's disease (AD) is a degenerative brain disease that poses an enormous economic and healthcare burden on society 1,2 . AD has been extensively investigated in modern medicine and communities worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…AD has been extensively investigated in modern medicine and communities worldwide. Currently, several targeted therapeutic strategies, including acetylcholinesterase inhibitors, β‐site amyloid precursor protein cleaving enzyme‐1 inhibitors, and N‐methyl‐D‐aspartate receptor antagonists, have been used clinically to alleviate the symptoms of AD 2–5 . However, there is currently no drug that can reverse the mechanisms underlying AD.…”
Section: Introductionmentioning
confidence: 99%
“…So far, however, compared with placebo in clinical trials, these monotherapies have failed to affect disease progression or symptoms (Dodel et al, 2003;Godyn et al, 2016;Panza et al, 2019). Recently, the scientists believe that combination therapy might be better than monotherapy (Bachurin et al, 2017;Sahoo et al, 2018;Cummings et al, 2019;Schaduangrat et al, 2019). However, the complex pathophysiology of AD makes the design of combination therapy more difficult.…”
Section: Introductionmentioning
confidence: 99%